Comparison between natural mating and artificial insemination in swine - Silveira, Paulo Roberto S. da (2014)
Data from 974 litters, being 78.33% produced by artificial insemination and 21.67% by natural mating, were analysed in order to compare the efficiency of the two methods. The data were collected in an industrial kind of swine operation. The average litter sire at birth, piglets born, piglets born alive, individual piglets weight and number of pigs weaned were respectively 10.92 ± 0.18; 10.74 ± 0.17; 1.50 ± 0.12 and 9.31 ± 0,17 for natural mating and 10.58 ± 0,11; 10.41 ± 0.10; 1.54 ± 0.09 and 9.14 ± 0.10 for artificial insemination. All of the contrasts between the parameters were analysed through the Student t-test and were not significant (P>0.05). First parity sows had no significant (P>0.05) differences between the two methods compared, but the pluriparous sows, naturally mated, had a significantly better performance (P<0.01) as for litter size at birth, piglets born alive and pigs weaned.